Power-Efficient Recycling Folded Cascode Operational Transconductance Amplifier Based on Nested Local Feedback and Adaptive Biasing - Chunkai Wu; Peng Cai; Jinghu Li; Jin Xie; Zhicong Luo (Sensors)
In this paper, we present a novel enhanced recycling folded cascode (ERFC) operational transconductance amplifier (OTA), which exhibits high efficiency and a fast transient response under weak inversion. Our innovative combination of adaptive biasing with nested local feedback (ABNLF) effectively enhances the input transconductance and slew rate (SR), thus improving the transient response. By incorporating coupling capacitors at the output stage, we achieve a stable operating region with large signal responses. Both the traditional RFC OTA and the proposed ERFC OTA were designed in a 0.18 <semantics>μ</semantics>m CMOS process, operating at a power supply of 1.8 V, with quiescent currents of 8 <semantics>μ</semantics>A and 10.4 <semantics>μ</semantics>A, respectively. Post-layout simulations reveal a remarkable enhancement in the proposed ERFC OTA over the traditional RFC OTA, with the SR and gain–bandwidth (GBW) surging by 120- and 5.95-fold, respectively. This advancement boosts the efficiency of the traditional RFC OTA and provides an impressive figure of merit (FoM) of 130.04 (V/<semantics>μ</semantics>s)·pF/<semantics>μ</semantics>A.